Performance of teeth of lingcod, Ophiodon elongatus, over ontogeny. Issue 2 (28th September 2015) - Galloway, Katherine A.; Anderson, Philip S.L.; Wilga, Cheryl D.; Summers, Adam P.
ABSTRACT: Fish teeth can play several roles during feeding; capture, retention, and processing. In many fish lineages teeth may be present on non‐jaw cranial bones that lack opposing teeth, such as the vomer and palatine. We hypothesized that teeth on different bones have different functions, and that the function of a set of teeth may vary over ontogeny. In this study, puncture, and draw performance of in situ vomerine teeth are compared to premaxillary teeth of the piscivorous lingcod, Ophiodon elongatus . The force required to pierce prey and to draw prey out of the mouth once the teeth were embedded was measured in ten individuals ranging from 205 to 836 mm SL to test for ontogenetic effects. Vomerine teeth in juvenile lingcod required proportionally less force to puncture prey items than adult lingcod, while premaxillary teeth showed the opposite trend. Draw force required to remove prey from the grasp of both toothed bones show the same shift with ontogeny. These results suggest that there is a shift in tooth function from vomerine to premaxillary teeth over ontogeny of lingcods. In juvenile lingcod, vomerine teeth function more effectively during initial puncture. In contrast, the premaxillary teeth pierce more effectively in adults. Juvenile lingcod are expected to use the premaxillary teeth while adult lingcod are expected to use the vomerine teeth to retain prey due to the larger force required for the prey to escape. The curvature of vomerine teeth increases over ontogeny suggesting increasing functional performance in retaining prey. J. Exp. Zool. 9999A:1–7, 2015. © 2015 Wiley Periodicals, Inc.